2010
DOI: 10.1038/ni.1941
|View full text |Cite
|
Sign up to set email alerts
|

The cytosolic exonuclease TREX1 inhibits the innate immune response to human immunodeficiency virus type 1

Abstract: Viral infection triggers innate immune sensors to produce type I interferons (IFN). However, HIV infection of T cells and macrophages does not trip these alarms. How HIV avoids activating nucleic acid sensors is unknown. The cytosolic exonuclease TREX1 suppressed IFN triggered by HIV. In Trex1−/− mouse cells and human CD4+ T cells and macrophages in which TREX1 was inhibited by RNA interference, cytosolic HIV DNA accumulated, and HIV infection induced type I IFN that inhibited HIV replication and spreading. TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
505
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(528 citation statements)
references
References 50 publications
(75 reference statements)
17
505
1
5
Order By: Relevance
“…Thus, the less stable glyco-Gag mutant capsid could allow intracellular sensors to more readily sense viral RNA or DNA. TREX1, an exonuclease present in the cytosol of macrophages and T cells, digests reverse-transcribed retroviral and retrotransposon DNA, thereby down-modulating the innate immune response to viral DNA by an as-of-yet unknown cytosolic sensor; in its absence, the innate immune response to retroviral RTCs or viral DNA is greatly increased (44,45). To determine whether the RTC of glyco-Gag mutant virions was more accessible to this cytosolic sensor, as well as to APOBEC3, NR-9456 macrophages were transfected with TREX1 siRNA and infected with WT and glyco-Gag mutant M-MLV.…”
Section: Apobec3 Restricts Endogenous Reverse Transcription Of Glyco-gagmentioning
confidence: 99%
“…Thus, the less stable glyco-Gag mutant capsid could allow intracellular sensors to more readily sense viral RNA or DNA. TREX1, an exonuclease present in the cytosol of macrophages and T cells, digests reverse-transcribed retroviral and retrotransposon DNA, thereby down-modulating the innate immune response to viral DNA by an as-of-yet unknown cytosolic sensor; in its absence, the innate immune response to retroviral RTCs or viral DNA is greatly increased (44,45). To determine whether the RTC of glyco-Gag mutant virions was more accessible to this cytosolic sensor, as well as to APOBEC3, NR-9456 macrophages were transfected with TREX1 siRNA and infected with WT and glyco-Gag mutant M-MLV.…”
Section: Apobec3 Restricts Endogenous Reverse Transcription Of Glyco-gagmentioning
confidence: 99%
“…This prevents detection of reverse‐transcribed viral DNA and activation of interferon responses (Gao et al , 2013; Bridgeman et al , 2015; Gentili et al , 2015). Other factors contributing to HIV‐1 escape in DCs have been described and include TREX1, an exonuclease that degrades reverse‐transcribed HIV DNA in the cytoplasm (Yan et al , 2010), and APOBEC3G/3F (A3G/3F) whose knockdown enhances HIV‐1 infection of DCs associated with G‐to‐A hypermutation of the HIV genome (Pion et al , 2006). These observations explain how HIV‐1 avoids innate sensing during uptake into DCs and in the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, proteins involved in autophagy have also been shown to have an impact on the innate immune signaling by STING (Saitoh et al, 2009). More recently, an exo-nuclease, TREX1 has been shown to indirectly regulate the activity of STING (Yan et al, 2010). Zhong et al (2008) first reported that phosphorylation of STING Ser358 by TBK1 is critical for activation of IRF-E. STING expressed in 293 cells infected with Sendai virus was readily phosphorylated by TBK1.…”
Section: Regulation Of Stingmentioning
confidence: 99%
“…More recently, human immunodeficiency virus (HIV) was shown to employ a cytoplasmic exo-nuclease, TREX1, to evade activation of STING-mediated innate immune signaling (Yan et al, 2010). Once inside the cell, the RNA of HIV is reverse transcribed into DNA and transported to the nucleus for integration into host chromosome.…”
Section: Proteinmentioning
confidence: 99%
See 1 more Smart Citation